Intravitreal dexamethasone implant one month before versus concomitant with cataract surgery in patients with diabetic macular oedema: the dexcat study. Issue 1 (26th June 2020) - Fallico, Matteo; Avitabile, Teresio; Castellino, Niccolò; Longo, Antonio; Russo, Andrea; Bonfiglio, Vincenza; Parisi, Francesca; Furino, Claudio; Panozzo, Giacomo; Scorcia, Vincenzo; Carnevali, Adriano; Bandello, Francesco; et al.
Abstract: Purpose: To report clinical outcomes of two different timings of intravitreal dexamethasone (DEX) implant administration for prevention of diabetic macular oedema (DME) worsening following cataract surgery. Methods: This multicentre, retrospective study included patients with DME who received an intravitreal DEX implant 1 month before cataract surgery, 'precataract DEX' group, or at the time of cataract surgery, 'concomitant treatments' group. Inclusion criteria were a follow‐up ≥3 months and ophthalmological examination with optical coherence tomography (OCT) imaging at baseline (cataract surgery) and throughout follow‐up. Anatomical improvement was considered to be a decrease in OCT central subfield (CSF) thickness ≥20% compared to baseline. The primary outcomes were anatomical and functional results at 3 months. Results: Two hundred twenty‐one patients were included: 136 in the 'precataract DEX' group and 85 in the 'concomitant treatments' group. At 3 months, a reduction of CSF thickness ≥ 20% was found in 7.3% of eyes in the 'precataract DEX group' and in 83.7% of eyes in the 'concomitant treatments' group (p < 0.001), with mean CSF thickness lower in the latter group (371 ± 52 µm versus 325 ± 57 µm, p < 0.001). At 3 months, mean best‐corrected visual acuity had improved from baseline in both groups (p < 0.001), with no difference between groups (p = 0. 20). No serious systemic adverse events were reported. Conclusion: Both approaches prevented a worsening of DME, showing a comparable visual outcome. Dexamethasone (DEX) implant given at the same time as cataract surgery provided a better anatomical outcome.